2020
DOI: 10.3390/biomedicines8070231
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Obesity in Children

Abstract: Asthma and obesity are two major chronic diseases in children and adolescents. Recent scientific evidence points out a causative role of obesity in asthma predisposition. However, studies assessing the real impact of excessive weight gain on lung function in children have shown heterogeneous results. In this review, the pathological mechanisms linking obesity and development of asthma in children are summarized and factors influencing this relationship are evaluated. Common disease modifying factors including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 91 publications
(118 reference statements)
0
38
1
2
Order By: Relevance
“…42 Leptin acts with Th1 cell differentiation, TNF-a, IFNgamma, and IL-6 increase. 43 Therefore, chronic lowgrade inflammation related to obesity may potentiate the effect of atopy on the deterioration of pulmonary functions in obese asthmatics more severely than that of non-obese asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…42 Leptin acts with Th1 cell differentiation, TNF-a, IFNgamma, and IL-6 increase. 43 Therefore, chronic lowgrade inflammation related to obesity may potentiate the effect of atopy on the deterioration of pulmonary functions in obese asthmatics more severely than that of non-obese asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies [ 17 , 18 , 19 , 20 ] demonstrated that in children overweight or obesity are risk factors for asthma development. Egan et al [ 16 ] examined six prospective cohort studies and reported that compared to normal weigh children, children with overweight or obesity have a 50% increased risk of physician-diagnosed asthma.…”
Section: Which Came First the Chicken Or The Egg?mentioning
confidence: 99%
“…In asthma animal models, T1DM was shown to increase the inhibitory neuronal muscarinic receptor function with an effect of reduction of airway hyperactivity [ 77 ]. On the contrary, in obese hyperinsulinemic children with asthma, the bronchial hyperresponsivity could be due to the increased acetylcholine production in bronchial smooth muscle cells by the insuline-M2 receptors interaction [ 78 , 79 ].…”
Section: Studies Reporting No Association Between Asthma and Type 1 Diabetesmentioning
confidence: 99%